2020
DOI: 10.1002/pen.25449
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of acetalization process of poly(vinyl alcohol) for the formation of crosslinked poly(vinyl formal) foams

Abstract: In the present work, poly(vinyl formal) (PVF) foams were prepared using water as the pore‐forming agent and formaldehyde as the crosslinking agent. The acetalization process of poly(vinyl alcohol) was exploited in depth in order to obtain a precise guidance on the preparation of PVF foams with adjustable properties. With the increasing of formaldehyde, the crosslinking degree was gradually increased and the prepared PVF foams changed to be amorphous. Morphology observation showed that the porous structure of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Prior to this, Nobuo Kimizuka et al reported the upconversion of an organic gel in which the dye pair gathers inside the fibers, which play a good role in shielding oxygen. 41 However, this system is far inferior to the PVA-C8 gel system in terms of transparency, quantum yield, and mechanical properties. In order to demonstrate its admirable mechanical properties, we knotted the gel and stretched it to about five times its original length without it being broken (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to this, Nobuo Kimizuka et al reported the upconversion of an organic gel in which the dye pair gathers inside the fibers, which play a good role in shielding oxygen. 41 However, this system is far inferior to the PVA-C8 gel system in terms of transparency, quantum yield, and mechanical properties. In order to demonstrate its admirable mechanical properties, we knotted the gel and stretched it to about five times its original length without it being broken (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…14 The three-dimensional polymer crosslinked network contains a large number of unique structural characteristics of solvent molecules, 34 and thus not only can it possess the performance merits of both classic fluorescent polymer solution and solid materials, but also present outstanding new properties such as inherent soft and humid characteristics, air stability, and stimulus responsiveness with multifunctional synergistic change characteristics. [35][36][37][38][39][40][41] This is also one of the significant development directions in the field of advanced light-emitting polymer materials. These materials include a continuous polymer network and a liquid organic phase in which the upconversion chromophores are dissolved.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the molar ratio between PVA and formaldehyde significantly alters foams' morphology. [ 23 ] PVA foams with 30 vol% loadings were chosen, and (PVA/GS‐30) and (PVA/GS‐30a) were prepared at two different molar ratios of OH: HCHO. They exhibit a difference in their morphology, porosity, and density.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7] Usually, PVA with a high degree of polymerization has strong intra-and intermolecular hydrogen bonds and can be used for the preparation of PVF foams. [8][9][10][11] In addition, to having the general properties of foam plastics, PVF foams have low toxicity with the advantage of being biodegradable and can be used in medicine, cleaning, washing, filtration, environmental protection, etc.. [12][13] The excellent performance of PVF foams is mainly due to internal pore structure.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the properties of PVA are also influenced by its degree of polymerization [6–7] . Usually, PVA with a high degree of polymerization has strong intra‐ and intermolecular hydrogen bonds and can be used for the preparation of PVF foams [8–11] . In addition, to having the general properties of foam plastics, PVF foams have low toxicity with the advantage of being biodegradable and can be used in medicine, cleaning, washing, filtration, environmental protection, etc.…”
Section: Introductionmentioning
confidence: 99%